2005
DOI: 10.1520/jfs2005160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Alzheimer's Disease in an Exhumed Decomposed Brain After Twenty Months of Burial in a Deep Grave

Abstract: After 20 months of interment in a deep grave, the decomposed body of the 81-year old testator of a will was exhumed to sustain the burden of proof that he lacked testamentary capacity when the will was rewritten two days prior to his death. The brain was mushy and pulverized with complete disappearance of the brainstem, cerebellum and subcortical ganglia. Small foci of relatively intact dorsal frontal neocortex were identified. Sections from these foci were stained with hematoxylin and eosin, bielchowsky silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
2
6
0
1
Order By: Relevance
“…This finding is confirmation of previously published studies demonstrating degradation of proteins with prolonged PMI (Ferrer et al 2007a;Crecelius et al 2008;Santpere et al 2006). However, it is notable that not all proteins degrade in a similar manner (Omalu et al 2005); therefore scientists should test the protein/enzyme of interest ahead for its sensitivity to degrade as consequence of pre-mortem of postmortem conditions.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is confirmation of previously published studies demonstrating degradation of proteins with prolonged PMI (Ferrer et al 2007a;Crecelius et al 2008;Santpere et al 2006). However, it is notable that not all proteins degrade in a similar manner (Omalu et al 2005); therefore scientists should test the protein/enzyme of interest ahead for its sensitivity to degrade as consequence of pre-mortem of postmortem conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies showed that stability of different microtubuli associated proteins and other antigens assessed by immunohistochemistry changes with increasing postmortem delay (0-72 h) and depends on storage temperature [5,11]. Recently, Alzheimer's disease has been successfully diagnosed in an exhumed decomposed human brain after 20 months of burial in a deep grave [15]. However, there are insufficient data on preservation of human brain tissue kept in situ for a prolonged time period.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, such repetitive TBI exposure may lead to chronic traumatic encephalopathy (CTE), a degenerative tauopathy. 3,4 Prevention of chronic symptomatologies and neurodegenerative disease after concussion is based on the avoidance of repeat exposure to TBI-producing events until patients become asymptomatic. This principle is at the root of several versions of return-to-play or combat guidelines issued by international conferences, clinical professional associations, the Centers for Disease Control and Prevention and the US military (http://www.dvbic.org).…”
Section: Introductionmentioning
confidence: 99%